A Survey of Cancelable Biometric Based Key Generation Scheme using various Cryptography Techniques - Joshi, KN; Chaudhari, P (International Journal of Computer Sciences and Engineering, 2025)
Key management in cryptosystem has more security concerns. In traditional cryptosystem key is generated randomly and very difficult to remember. The keys generated from biometric features provide better option than traditional cryptographic key management techniques such as password based key generations. Cancelable biometric is a customized technique in biometric based cryptography, where Cancelable Biometric refers to the intentional and systematically repeatable distortion of biometric features in order to protect sensitive user-specific data. This paper presents the survey conducted for same of the cancelable biometric key generation techniques.